Effect of Preoperative Bicarbonate Infusion on Maternal and Perinatal Outcomes of Obstructed Labour in Mbale Regional Referral Hospital: a study protocol for a randomised controlled trial - Musaba, Milton W.; Barageine, Justus K.; Ndeezi, Grace; Wandabwa, Julius N.; Andrew, Weeks (BMJ open, 2019)
To improve maternal and fetal outcomes among patients with obstructed labour (OL) in low-resource settings, the associated electrolyte and metabolic derangements must be adequately corrected. Oral fluid intake during labour and preoperative intravenous fluid replacement following OL corrects the associated dehydration and electrolyte changes, but it does not completely reverse the metabolic acidosis, that is, a cause of intrapartum birth asphyxia and a risk factor for primary postpartum haemorrhage due to uterine atony. Sodium bicarbonate is a safe, effective, cheap and readily available acid buffer, that is widely used by sportspeople to improve performance. It also appears to improve fetal and maternal outcomes in abnormally progressing labour. However, its effects on maternal and fetal outcomes among patients with OL is unknown. We aim at establishing the effect of a single-dose preoperative infusion of sodium bicarbonate on maternal and fetal lactate levels and clinical outcomes among patients with OL.